Evaluasi Kesesuaian Jalur Trayek BRT Trans Sidoarjo Terhadap Pengembangan Antar CBD - Suning Suning; Pungut Pungut (UIN Sultan Syarif Kasim Riau, 2016)
Sidoarjo Regency is one of the main economic growth in the East Java which has CentralBussiness District (CBD) spreading over the region includes the Buduran District, Candi District andSidoarjo City District. As the main hub of Sidoarjo regional growth, Sidoarjo City has implemented theconcept of environment-friendly transportation of Bus Rapid Transit (BRT) to connect the economic spots.BRT has operating since 2015 on a certain bus routes through 14 stops with 15 Buses. Previous studyshows the road level of service that connects between urban economic spot in Sidoarjo have an averagevalue of the degree of saturation (DS) > 1, causing traffic jams, low speed and volume exceeds capacity.The level of transportation services has affect the accessibility of the traffic lane between the CBD withBRT passing through Jl. Raya Candi, Jl. Sunandar, Jl. Pahlawan, bypassing the CBD in the Buduran area.Therefore, it is important to investigate the suitability of the route of BRT lane towards the development ofeach CBD and its connectivity. This study aims to identify the problems of operational performance ofBRT, which has been implemented based on the bus routes by the city government. This empirical studyused both qualitative and quantitative method with data collection through surveys on bus and interviewswith bus passenger. This study used the comparative analysis of the empirical data with the standard ofDirjen. of Land and Transportation No. 687 Yr 2002. The research finding shows that the public interest inusing BRT is low, which load factor only 43%, compared to a load factor based on the standard of Dirjen ofLand Transportation by 70%. Moreover, only 58% of BRT facility is in compliance with the minimumstandards of the Ministerial Regulation No. 27 Yr. 2015 on the BRT. Therefore, it needs to determine anew policy with regard to the route of BRT lane Trans Sidoarjo in accordance with the development ofinter-CBD in the Sidoarjo City.Keywords: Bus Rapid Transit (BRT), bus route, CBD, Sidoarjo city, transportation